PENGARUH KINERJA DEWAN PERWAKILAN RAKYAT DAERAH OGAN KOMERING ULU TERHADAP TINGKAT KEPERCAYAAN PUBLIK PASCA OPERASI TANGKAP TANGAN OLEH KOMISI PEMBERANTASAN KORUPSI TAHUN 2025 - Putra, M. Nasir Nandi; Aprilia Lestari; Herni Ramayanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Public trust constitutes the main foundation of the legitimacy of legislative institutions within a local democratic system. In 2025, a sting operation conducted by the Corruption Eradication Commission against membersi of the Regional People’s Representative Council of Ogan Komering Ulu Regency triggered a crisis of public trust toward the institution. This study focuses on examining the extent to which the performance of the Regional People’s Representative Council of Ogan Komering Ulu Regency influences the level of public trust following the sting operation. The objectivesi of thisi research are to analyze the effect of DPRD performance on public trust and to identify efforts to restore the legitimacy of the local legislative institution. This study employs public trust and legitimacy theories as the main theoretical framework to explain the relationshiip between the performaince of public institutions and public support. A quantitative approach with a survey method was used. The research was conducted in Ogan Komering Ulu Regency in 2025, involving 100 respondents selected through purposive sampling. Data were collected using a closed-ended questvionnaire, while data analysis was performed using simple linear regression, a t-test, and the coefficient of determination. The findings indicate that the performance of the Regional People’s Representative Council has a significant effect on the level of public trust, with a coefficient of determination of 0.582, meaning that DPRD performance accounts for 58.2% of the viariation in public trust. The conclusion of this study confirms that improving DPRD performance is crucial for restoring public trust after the sting operation. Therefore, it is recommended that the Regional People’s Representative Council enhance transparency, accountability, and public communication to strengthen institutional legitimacy and public trust.